Monitoring Kualitas Air Laut Teluk Lamong Berdasar Bioindikator Plankton Dan Benthos - Sophia Alvin Nurina Yulia Masladen; Praditya Sigit Ardisty Sitogasa (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Lamong Bay is one of the important water areas in Indonesia, located around the coastal area of ​​Surabaya, East Java. This area has high ecological and economic value because it functions as a sea transportation route and supports marine biota. So this research is intended to monitor the quality of sea water in Lamong Bay based on benthos and plankton bioindicators. Plankton and benthos are small organisms that live in waters and are very sensitive to environmental changes. The plankton sampling method involves using a plankton net to collect plankton samples from the waters. The grab and net sampling method is a method used to collect benthos samples from the bottom of the waters. The results that can be concluded from the analysis carried out in the waters of Lamong Bay, for the type and abundance of plankton, phytoplankton are 3 classes, namely Bacillariophyta (16 species), Cyanobacteria (2 species), and Euglenozoa (1 species), and zooplankton found include Arthropods Monacilla sp. and Nauplius, Ciliophora individuals include Favella sp. , Tintinnopsis sp. , Tintinnopsis sp. 2, Tintinnopsis sp. 3 as well as individual Rotifera including Notholca sp. Meanwhile, for Benthos, only Thiaridae was found.